PELATIHAN MENELUSURI SUMBER REFERENSI DAN MENGGUNAKAN APLIKASI REFERENCE MANAGER UNTUK MENINGKATKAN KESIAPAN PENULISAN TUGAS AKHIR MAHASISWA - Terrylina Arvinta Monoarfa; Osly Usman; Umi Widyastuti; Shandy Aditya; Diena Noviarini; Meta Bara Berutu (Indonesian Collaboration Journal of Community Services, 2023)
Research activities are generally carried out by students as part of the completion of the final project (thesis) which is one of the graduation requirements for obtaining a bachelor's degree. There are several reference sources that can be used as references in conducting research, including textbooks, previous research journal articles, data and information published by official institutions, as well as results of observations or preliminary research. With a complete reference source, it is expected that students can easily conduct research and write their final project. This community service activity seeks to provide training and practical instructions in accessing national and international journal articles, as well as the process of writing final assignments and publishing scientific articles. This community service activity aims to accelerate students' ability to complete their final project, as an implementation of a cooperation agreement that has been agreed upon by the Faculty of Economics, Jakarta State University with several universities in Indonesia. The time for implementing this community service activity is October 15th  2022. The training was be carried out via media zoom, bearing in mind that currently, Indonesia is still in a pandemic period so there are limitations to conducting face-to-face learning. For this reason, various tips will be explained through this training on how to access various research reference sources that can be carried out by optimizing the use of digital applications. It is hoped that through this training, FE UNJ can actively collaborate with other tertiary institutions in Indonesia in improving capabilities and accelerating the completion of student final assignments in Indonesia